163 LIGAMENT ENGINEERING: CHARACTERISTICS OF BETA FIBROBLAST GROWTH FACTOR RELEASE FROM A BIOENGINEERED SCAFFOLD. Issue 1 (1st January 2007) - Barba, D.; Sun, V.; Esmende, S.; Petrigliano, F.; Kamei, D.; McAllister, D.; Wu, B.
Abstract : The anterior cruciate ligament is a commonly injured ligament of the knee in which ligament reconstruction with a graft is necessary due to its limited healing capacity. With limitations on the existing graft alternatives, we aim to engineer a ligament using a donor's bone marrow stromal cells (BMSCs). Recently, our laboratory reported synergism between biomechanical and biochemical stimulation (bFGF) resulting in up-regulation of gene expression of stress-resistant collagen I and stress-responsive collagen III and tenascin-C. However, it was unclear if this observation was due to true synergism between mechanical and biochemical signal transduction pathways or due to enhanced release kinetics of the bFGF. The objective of this project is to determine the effects of mechanical stimulation on the release kinetics of bFGF in the presence of a complex biologic environment (cells, media, etc.). Microporous scaffolds were constructed from biodegradable polycaprolactone polymers, loaded with 400 ng I-125-labeled bFGF per scaffold and seeded with BMSCs harvested from rats. Release of bFGF was quantified by measuring radioactivity from I-125-labeled bFGF on either strained (6%) or unstrained scaffolds. After 10 hours, approximately 30% of the bFGF was burst-released from the scaffolds, 10% of bFGF was released after 6 days, and approximately 60% remained on the scaffolds. Mechanical stimulation did not affect the release of bFGF within this complex biologic environment. In summary, we have established and characterized a controlled release system to deliver bFGF to cells seeded within microporous scaffolds and subjected to biomechanical stimulation. Given that the release kinetics are not influenced by mechanical stimulation, this system allows us to uncouple the effects of mechanical stimulation and growth factor delivery in future experiments. This finding also encourages the investigation of common signal transduction pathways that may be involved in the observed synergism between biomechanical and biochemical stimulation.